A new species of Calochromus Guérin-Méneville (Coleoptera: Lycidae) from Fiji - Ramsdale, Alistair S. (Zootaxa, 2007)
Calochromus samuelsoni sp. nov. is described from Viti Levu, Fiji. Photographs of its habitus, antenna and aedeagus are presented. This new species represents the first record of the genus Calochromus and the subfamily Calochrominae (Coleoptera: Lycidae) from Fiji.